The Influence of Soil Health on Food Security and Nutrition: A Review (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
This paper provided a review on the crucial role of soil in food production, nutritional quality, and sustainable agricultural practices. By analyzing soil composition and nutrient availability, soil management practices for sustainable agriculture, soil microorganisms and food safety, soil contamination and food quality, soil health and nutritional quality of crops, impact of climate change on soil fertility and food production, future perspectives and innovation, this article aimed to enhance our understanding of the interconnections between soil and food, ultimately contributing to the development of innovative agricultural practices and improved food security.
Keywords: Food security; Soil health; Soil nutrient dynamics; Sustainable agriculture